Synthetic control over proximity of metal and acid dual sites switches the selectivity of acetophenone hydrodeoxygenation - Luyan Li; Xinhui Guo; Jiajia Huang; Zhenhe Jia; Xiaoshuo Liu; Qiaoqiao Guan; Yu Gu; Weijie Yang; Junling Lu; Shaojun Guo; Hai-Long Jiang (Proceedings of the National Academy of Sciences, 2026)
Though spatial arrangement between metal and acid has proven efficiency for enhancing catalytic performance, their precise regulation on controlling the product selectivity and revealing related catalytic mechanism remains scarce. Herein, we report a class of Pd nanoparticles integrated into isoreticular UiO-66-type metal-organic frameworks with or without sulfonic acid groups (denoted UiO-S and UiO), which allows for precise distance tuning between Pd and acid site by controlling UiO-66 interlayer thickness. Unlike traditional studies focusing on substrate/intermediate diffusion by dual-site regulation, we herein demonstrate that significant modulation of electron transfer and proton concentration around Pd over UiO-S@UiO 25 @Pd@UiO switches reaction pathways and profoundly tunes selectivity in acetophenone hydrodeoxygenation. Specifically, we show that UiO-S@UiO 25 @Pd@UiO with a 25 nm separation between Pd and acid sites achieves the highest selectivity (~94%) to phenylethanol via homolytic H 2 cleavage, mitigating prevalent overhydrogenation pathway; whereas UiO-S@Pd@UiO and UiO@Pd@UiO-S, with closely positioned dual sites, dramatically enhance hydrodeoxygenation activity, and display >99% selectivity to high-energy-density ethylbenzene. Notably, a proton-assisted mechanism involving H 2 heterolysis is elucidated over UiO@Pd@UiO-S, particularly significant for implementing the catalytic process under mild conditions.